Assessing the Covalent Attachment and Energy Transfer Capabilities of Upconverting Phosphors With Cofactor Containing Bioactive Enzymes - Burgess, Letitia; Wilson, Hannah; Jones, Alex R.; Hay, Sam; Natrajan, Louise S. (Frontiers in Chemistry, 2020)
Upconverting phosphors (UCPs) convert multiple low energy photons into higher energy emission via the process of photon upconversion and offer an attractive alternative to organic fluorophores for use as luminescent probes. Examples of biosensors utilizing the apparent energy transfer of UCPs and nanophosphors (UCNPs) with biomolecules have started to appear in the literature but very few exploit the covalent anchoring of the biomolecule to the surface of the UCP to improve the sensitivity of the systems. Here, we demonstrate a robust and versatile method for the covalent attachment of biomolecules to the surface of a variety of UCPs and UCNPs in which the UCPs were capped with functionalized silica in order to provide a surface to covalently conjugate biomolecules with surface-accessible cysteines. Variants of BM3Heme, cytochrome C, glucose oxidase and glutathione reductase were then attached via maleimide-thiol coupling. BM3Heme, glucose oxidase and glutathione reductase were shown to retain their activity when coupled to the UCPs potentially opening up opportunities for biosensing applications.